Ancient literature for New Testament studies - Evans, Craig A. 1952-; Wassen, Cecilia 1962-; Collins, Adela Yarbro 1945-; Collins, John J. 1946-; Macaskill, Grant; Johnson, Nathan C. 19XX- (Zondervan Academic, 2024)
"Ancient Literature for New Testament Studies is a 10-volume series that introduces key ancient texts that form the cultural, historical, and literary context for the study of the New Testament. Neither too technical to be used by students nor too thin on interpretive information to be useful for serious study of the New Testament, this series provides a much needed resource for understanding the New Testament in its Jewish, Greco-Roman, and early Christian contexts [...]."